Hydnotrya qinghaiensis sp. nov. (Discinaceae, Pezizales) from Tibetan Plateau, China - Xu, Ao; Lu, Jiao-Jiao; Lin, Wen-Fei; Fan, Li; Xie, Meng-Le; Wan, Shan-Ping; Li, Yi (Phytotaxa, 2023)
Hydnotrya qinghaiensis, a new species, is described from Tibetan Plateau, China. It is characterized by the irregular globose, brownish and large ascomata. Morphologically, the new species differs from the closely related H. cerebriformis and H. variiformis by the color, size, and shape of the ascocarp and the shape of ascospores. A detailed description and comparison with closely related species are provided, and the phylogenetic placement of the new species is also discussed based on the nuclear internal transcribed spacer region (ITS).